IDDF2022-ABS-0020 The impact of interprocedure radiological characteristics to the outcomes of intermediate stage hepatocellular carcinoma receiving transcatheter arterial chemoembolization. (2nd September 2022) - Lee, Shao-Wu; Cheng, Yu-Chi; Yen, Chieh-Ling; Lee, Teng-Yu
Abstract : Background: Transcatheter arterial chemoembolization (TACE) is the recommended treatment modality for intermediate-stage hepatocellular carcinoma (HCC). The aim of this study was to determine the HCC radiological characteristics associated with the prognosis of patients with intermediate-stage HCC receiving TACE. Methods: Patients with BCLC stage B HCC from January 2005 to December 2009 were collected. Patients with complete response or partial response were assigned to the objective response (OR) group, while others were non-OR group. The radiological characteristics, as well as survival rates of these two groups, were compared. Results: Among a total of 176 patients, there were 66(51.6%) and 62(48.4%) cases in the OR group and non-OR group, respectively. The logistic analysis found that combined radiological characteristics, including complete lipiodol retention, tumor feeding artery blockage, and no residual tumor blush were significantly correlated with achievement of OR (HR 2.46, 95% CI 1.08–5.61, 9=0.032). However, no radiological characteristics had significant strength in predicting overall survival. Patients with OR after TACE had a significantly longer overall survival than those with non-OR (25.80 vs. 15.15 months, p=0.035). Conclusions: Combined radiological characteristics of complete lipiodol retention, tumor feeding artery blockage and no residual tumor blush had s positive impact on OR in TACE. In patients receiving TACE, those who achieved OR had better overall survival.